2004
DOI: 10.1136/oem.2003.008227
|View full text |Cite
|
Sign up to set email alerts
|

Increased inflammation and altered macrophage chemotactic responses caused by two ultrafine particle types

Abstract: Background:Ultrafine particles have been hypothesised to be an important contributing factor in the toxicity and adverse health effects of particulate air pollution (PM10) and nanoparticles are used increasingly in industrial processes.Aims:To compare the ability of ultrafine and fine particles of titanium dioxide and carbon black to induce inflammation, cause epithelial injury, and affect the alveolar macrophage clearance functions of phagocytosis and chemotaxis in vivo.Methods:Rats were instilled with fine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
197
1
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(218 citation statements)
references
References 28 publications
15
197
1
5
Order By: Relevance
“…In the present study, hamster lung fibroblast cells were chosen to investigate the toxicity of TiO 2 particles because the lung is the primary target organ of TiO 2 particle toxicity (Baan et al, 2006;Rothen-Rutishauser et al, 2006), using concentrations that were relevant to those that induced toxicity in earlier in vivo studies. For example, lung epithelial injury and toxicity were identified in rats after exposure to 1000 mg/L of ultrafine TiO 2 (29 nm), and DNA damage was detected in the blood cells of the mice treated with P25 (300 mg/L) for 5 d (Renwick et al, 2004;Trouiller et al, 2009;Warheit et al, 2007). It is noteworthy that the response of rats to insoluble-particle "lung overload" is stereotyped and unique to that species.…”
Section: Most Of the Toxicological Results On Nps Have Been Generatedmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, hamster lung fibroblast cells were chosen to investigate the toxicity of TiO 2 particles because the lung is the primary target organ of TiO 2 particle toxicity (Baan et al, 2006;Rothen-Rutishauser et al, 2006), using concentrations that were relevant to those that induced toxicity in earlier in vivo studies. For example, lung epithelial injury and toxicity were identified in rats after exposure to 1000 mg/L of ultrafine TiO 2 (29 nm), and DNA damage was detected in the blood cells of the mice treated with P25 (300 mg/L) for 5 d (Renwick et al, 2004;Trouiller et al, 2009;Warheit et al, 2007). It is noteworthy that the response of rats to insoluble-particle "lung overload" is stereotyped and unique to that species.…”
Section: Most Of the Toxicological Results On Nps Have Been Generatedmentioning
confidence: 97%
“…The photocatalytic activity and cytotoxicity of the anatase nano-TiO 2 are higher than that of the rutile form (Kakinoki et al, 2004;Sayes et al, 2006). Similarly, several studies suggested that lung inflammation and consequently cancer in rats could be induced after inhalation and intratracheal instillation of TiO 2 nanoparticles, with stronger inflammogenic activity in comparison with its micron-sized counterpart (Donaldson et al, 2002;Falck et al, 2009;Renwick et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…It has the capacity to absorb radiation and is the principle factor in the reduction of visibility caused by air pollution 114 . Experimental and epidemiological studies show that exposure to ultrafine particles of BC are associated with increases in inflammatory cells, reduced alveolar macrophage activity and cardiovascular disease 115,116 .…”
Section: (H)mentioning
confidence: 99%
“…Indeed, ultrafine particles (aerodynamic diameter <100 nm) are responsible for a greater impact upon inflammation and macrophage function as compared to that evinced by fine particles (diameter 100 nm-2.5 µm) (Renwick et al, 2001(Renwick et al, , 2004. Thus, it is absolutely necessary to take into account the size of particles, onto which PAH are adsorbed, in order to obtain a more complete evaluation of potential immunotoxic effects.…”
Section: Introductionmentioning
confidence: 99%